THE EFFECT OF MANAGERIAL OWNERSHIP AND CORPORATE SOCIAL RESPONSIBILITY ON TAX AVOIDANCE - Antonia Pramudita; Puji Rahayu; Rike Selviasari (Multidiciplinary Output Research For Actual and International Issue (MORFAI), 2025)
Main Purpose - This study aims to analyze the effect of managerial ownership and corporate social responsibility (CSR) on tax avoidance practices in food and beverage sector companies listed on the Indonesia Stock Exchange (IDX) during the period 2020 to 2023. Method - This research employs a quantitative approach using multiple linear regression analysis to examine the relationships between the variables. Secondary data were obtained from annual reports and sustainability reports published by the selected food and beverage companies during the observation period. Main Findings - The results of this research reveal a complex interaction between non-financial factors—such as sustainability and CSR reporting and financial components like firm performance, in the context of tax avoidance practices. Theory and Practical Implications - The results indicate a significant and complex relationship between managerial ownership, CSR, and tax avoidance. Managerial ownership may lead to either aggressive tax avoidance or prudent fiscal behavior, depending on managerial incentives and long-term orientation. Meanwhile, CSR serves a dual role as both a tool of legitimacy and a compliance signal, which can either reinforce or reduce a firm's tendency toward tax avoidance. Novelty - This study fills a gap in the literature by simultaneously examining the effect of managerial ownership and CSR on tax avoidance in the context of developing countries, particularly the food and beverage sector in Indonesia, which has not been widely explored previously.